THE EFFECT OF PERMISSIVE PARENTING ON ACADEMIC SELF-EFFICACY THROUGH SOCIAL SUPPORT FOR PAI STUDENTS AT UNIVERSITAS AL-WASHLIYAH MEDAN - Nirmalasari, Susanti; Hasanuddin, Hasanuddin; Dewi, Salamiah Sari (Asosiasi Dosen Perguruan Tinggi Islam, 2024)
The purpose of this study was to analyze the direct effect of permissive parenting on students' academic self-efficacy and to construct a model that is in accordance with the standard value of the fit index. This research method uses a quantitative method. The population in this study were all PAI students at Al-Washliyah University, Medan, totaling 488 students. The sampling technique used was the total sampling technique. This study uses a mediation model approach (Neuman, 2013). This study will look at the function of the social support variable (M) on the effect of permissive parenting on academic self-efficacy. Based on the results of the analysis, it is known that permissive parenting has a significant negative effect on academic self-efficacy, with an estimated value of ? = -0.029 and p = 0.049. Based on the results of the analysis, it is known that there is an effect of family support on academic self-efficacy with an estimated value of ? = 0.145 and p = 0.006. Next, there is an influence of friend support on academic self-efficacy with an estimated value of ? = 0.229 and p = <0.001. Then, there is no significant influence of someone's support on academic self-efficacy, with an estimated value of ? = -0.075 and p = 0.129. The determining factor for learning success is the students themselves, so based on the results of this research, advice that can be given to students is to always pay attention to their intelligence and personality.